Publishing Blackness Textual Constructions of Race Since 1850 - Hutchinson, George B.; Young, John K. (Editorial Theory and Literary Criticism, 2013)
From the white editorial authentication of slave narratives, to the cultural hybridity of the Harlem Renaissance, to the overtly independent publications of the Black Arts Movement, to the commercial power of Oprah's Book Club, African American textuality has been uniquely shaped by the contests for cultural power inherent in literary production and distribution. Always haunted by the commodification of blackness, African American literary production interfaces with the processes of publication and distribution in particularly charged ways. An energetic exploration of the struggles and complexities of African American print culture, this collection ranges across the history of African American literature, and the authors have much to contribute on such issues as editorial and archival preservation, canonization, and the "packaging" and repackaging of black-authored texts. Publishing Blackness aims to project African Americanist scholarship into the discourse of textual scholarship, provoking further work in a vital area of literary study.